Synthesis, Characterization and Biological Activates Studies of some New Derivatives From 2-aminoo-5-mercapto-1, 3, 4-thiadiazole (Baghdad Science Journal, 2018)
In this work, thiadiazole derivatives were prepared by taking advantage of active sites in (2-amino-5-mercapto-1, 3, 4-thiadiazole) as a starting material base. The main heterocyclic compounds (1, 3, 4-thiadiazole, oxazole) etc, 2-amino-5-mercapto-1,3,4-thiadiazole compound (1) was prepared by cyclic closure of thiosemicarbazide compound with anhydrous sodium carbonate and carbon disulfide. Oxidation of (1) via hydrogen peroxide, to have (2) which was treated with chloro acetyl chloride to get (3). Preparation of thiazole ring (4) was from reacting of (3) with thiourea. Synthesis of diazonium salts (5) from compound (4) using sodium nitrite and HCl. Compound (5) reacted with different ester compounds to prepare a new azo compounds (6–8).Compound (3) reacts with viruses secondary amine to prepare compound (9–11). Full characterization of the synthesized compounds was done by using spectroscopic analysis such as FT-IR, 1H-NMR and C.H.N.S. technique.